Flavonol Glycosides from Saussurea controversa and Their Efficiency in Experimental Osteomyelitis - Avdeeva, Elena; Shults, Elvira; Skorokhodova, Marina; Reshetov, Yaroslav; Porokhova, Ekaterina; Sukhodolo, Irina; Krasnov, Efim; Belousov, Mikhail (Planta Medica International Open, 2018)
Five flavonoids were isolated from leaves of Saussurea controversa, one new flavonoid (5), three described for the first time from the genus Saussurea (1, 2, and 4), and one described previously (3). A number of flavonol glycosides can be easily isolated from the butanol fraction of the ethanol extract from S. controversa. As a result of separating these using column chromatography on silica gel and microcrystalline cellulose, five glycosides of quercetin were isolated in the proportional relationship of 2 (1): 8 (2): 10 (3): 1 (4): 4 (5). The structure of these substances was determined using the method of NMR by conducting various 1H-1H and 1H-13C correlation spectroscopy experiments and by comparing their spectroscopic data with published values, 5,3/,4/-trihydroxyflavone-7-О-α-L-rhamnopyranoside-3-О-β-D-glucopyranosidе (1), 5,7,3/,4/-tetrahydroxyflavone-3-О-β-D-glucopyranoside-(1→6)-β-D-glucopyranoside-(1→6)-О-α-L-rhamnopyranoside (2), 5,7,3/,4/-tetrahydroxyflavone-3-О-β-D-glucopyranoside-(1→6)-О-α-L-rhamnopyranoside (3), 5,3/,4/-trihydroxyflavone-7-О-α-L-rhamnopyranoside-3-О-β-D-xylopyranoside (4), and 5,3/,4/-trihydroxyflavone-7-О-β-D-glucopyranoside-3-O-α-L-rhamnopyranoside-(1→2)-О-β-D-glucopyranoside (5). It was established for the first time that flavonol glycosides from S. controversa stimulate granulopoiesis and lymphopoiesis in the bone marrow of rats, and enhance the reparative process in the affected area in experimental osteomyelitis.
Keywords: Saussurea controversa; Asteraceae; flavonol glycosides; experimental osteomyelitis; bone marrow; bone tissue